A prevalence study of platelet alloantibodies in multiply transfused thrombocytopenic patients in HUSM - Mahmood, Wan Haslindawani Wan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
BACKGROUND: Multiply transfused patients are frequently subjected to platelet alloimmunization. These platelet alloantibodies produced can result in refractoriness to platelet transfusion. STUDY DESIGN AND METHODS: Ninety five thrombocytopenic (platelet count <1 00 x 1 09/1) and multilply transfused (more than 2 times transfusion of any blood component with last transfusion more than 2 weeks prior to the study) patients were recruited prospectively. The blood samples were tested using a Solid Phase system (Capture P). RESULTS: There were 45 males (47.4%) and 50 females (52.6%) recruited with ages from 3 to 90 years. The frequency of transfusions ranged from 10-168. Seven patients (7.4%) were detected to have platelet alloantibodies, predominantly anti-HPA-5b in 4 patients (4.2%). Three of them (3.2%) showed a non-specific pattern. Six patients (6.3%) had received packed cells less than 20 units and another 1 (1.1%) received more than 20 units of packed cells. Four patients (4.2%) received platelet transfusion of less than 20 units and another 3 patients (3.2%) received more than 20 unit platelets. CONCLUSION: The study may have future implications for the selection of platelet donors for alloimmunized recipients in HUSM.